Decitabine-based treatment strategy improved the outcome of HSCT in JMML: a retrospective cohort study - Peng, Zhiyong; Gao, Jingyu; Huang, Litao; He, Yuelin; Tang, Haoran; Zong, Sa; Pei, Yanru; Pei, Fuyu; Ge, Jing; Liu, Xuan; Yue, Li; Zhou, Jun; et al. (Frontiers in Immunology, 2024)
Pre-HSCT disease control, suboptimal long-term prognosis, and a high recurrence incidence (RI) continue to pose significant challenges for hematopoietic stem cell transplantation (HSCT) in juvenile myelomonocytic leukemia (JMML) patients. This retrospective cohort study assessed the effectiveness of a decitabine (DAC)-based protocol in JMML patients undergoing HSCT.The pre-HSCT treatment includes initial and bridging treatment. The efficacy of DAC monotherapy versus DAC combined with chemotherapy (C-DAC) as initial treatment was compared, followed by DAC plus FLAG (fludarabine, cytarabine, and GCSF) as bridging treatment. The HSCT regimens were based on DAC, fludarabine, and busulfan. Post-HSCT, low-dose DAC was used as maintenance. The study endpoints focused on pretransplantation simplified clinical response and post-HSCT survival.There were 109 patients, including 45 receiving DAC monotherapy and 64 undergoing C-DAC treatment. 106 patients completed bridging treatment. All patients were administered planned HSCT regimens and post-HSCT treatment. The initial treatment resulted in 88.1% of patients achieving clinical remission without a significant difference between the DAC and C-DAC groups (p=0.769). Clinical remission rates significantly improved following bridging treatment (p=0.015). The 5-year overall survival, leukemia-free survival, and RI were 92.2%, 88.4%, and 8.0%, respectively. A poor clinical response to pre-HSCT treatment emerged as a risk factor for OS (hazard ratio: 9.8, 95% CI: 2.3-41.1, p=0.002). Implementing a DAC-based administration strategy throughout the pre-HSCT period, during HSCT regimens, and in post-HSCT maintenance significantly reduced relapse and improved survival in JMML patients. Both DAC monotherapy and the DAC plus FLAG protocol proved effective as pre-HSCT treatments.